2016
DOI: 10.1016/j.envpol.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

A proposal of “core enzyme” bioindicator in long-term Pb-Zn ore pollution areas based on topsoil property analysis

Abstract: To study the effects of long-term mining activities on the agricultural soil quality of Mengnuo town in Yunnan province, China, the heavy metal and soil enzyme activities of soil samples from 47 sites were examined. The results showed that long-term mining processes led to point source heavy metal pollution and Pb, Cd, Zn and As were the primary metal pollutants. Polyphenoloxidase was found the most sensitive soil enzyme activity and significantly correlated with almost all the metals (P < 0.05). Amylase (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 66 publications
2
56
0
Order By: Relevance
“…Currently, no quantitative standard of soil enzyme activity has been set to assess the level of heavy metal soil pollution. Generally, high enzyme activity represents good soil quality, while low activity may be related to the toxicity of pollutants to biological processes [8,54]. The urease enzyme (URE) plays an important role in the N cycle [55], it is loosely present in soil and is more often bound to soil organic matter or clay particles.…”
Section: Degree Of Contamination (C D )mentioning
confidence: 99%
“…Currently, no quantitative standard of soil enzyme activity has been set to assess the level of heavy metal soil pollution. Generally, high enzyme activity represents good soil quality, while low activity may be related to the toxicity of pollutants to biological processes [8,54]. The urease enzyme (URE) plays an important role in the N cycle [55], it is loosely present in soil and is more often bound to soil organic matter or clay particles.…”
Section: Degree Of Contamination (C D )mentioning
confidence: 99%
“…In recent years, heavy metal contamination of soils has become a serious issue not only to agricultural production, but also to the ecosystem health. The non-biodegradable nature of heavy metals, undoubtedly, leads to their accumulation of toxic levels which have resulted in several destructive effects on human health as well as the environment (Xiao et al 2017;Yang et al 2016). It is reported that globally, there are more than 5 million contaminated sites covering 20 million hectares of land in which the soils are contaminated by the heavy metal(loid)s As, Cd, Pb, Co, Cr, Hg, Cu, Ni, Zn, and Se with the present soil concentrations higher than the geo-baseline or regulatory levels (He et al 2015;Wuana and Okieimen 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This result can be interpreted that much higher Pb concentration compared to Cd in soil inhibits microbial activity, resulting in reduced phosphatase activity, while impact of soluble Cd on inhibition of microbial activity was minimal. In addition, phosphatase activity could be more sensitive than β-glucosidase activity when soil is polluted with heavy metals [29,57]. Yang et al [29] tested two different soil enzymes, oxidoreductase and hydrolase, to select the bio-indicator for evaluating heavy metal pollution in soil.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
“…In addition, phosphatase activity could be more sensitive than β-glucosidase activity when soil is polluted with heavy metals [29,57]. Yang et al [29] tested two different soil enzymes, oxidoreductase and hydrolase, to select the bio-indicator for evaluating heavy metal pollution in soil. This study revealed that amylase (for C cycling), acid phosphatase (for P cycling), and catalase (for redox reaction) was sensitive to heavy metal pollution showing significantly positive correlation (p < 0.05) with Pb, Cd, Zn concentration.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation